Countries And The Minerals Industry (The National Institute for Occupational Safety and Health (NIOSH), 1981)
U.S. Minerals Coordinating Council Advised. -The Critical Materials Act of 1981, H. R. 4281, introduced on July 27, would create a Council on Critical Materials in the White House Executive Office to oversee Federal materials programs involving $1 billion committed to research by 14 agencies, and to serve as the President's focal point to evaluate materials policy. It was introduced by Congressman Fuqua (D-Fla.) whose Committee on Science and Technology has over-sight over the implementation of P. L. 96-479, the National Materials and Minerals Policy, Research and Development Act of 1980. Bulgaria's Mineral Bank. -Recently Bulgaria established a mineral bank to facilitate receipt of foreign credits for exploiting Bulgaria's mineral raw materials. The bank has wide powers to enter into business arrangements with foreign creditors. Bulgaria's main interest in trading with the West is to import the technology for developing energy and mineral resources.